Nursing workload measurement scales in Intensive Care Units. Correlation between NAS and NEMS - Montserrat Martínez Lareo; Francisco Javier Carmona Monge; Gloria Mª Rollán Rodríguez; Cristina Quirós Herranz; Sonia García Gómez; Ana Jara Pérez; Rosana Alameda Varela; Isabel Cerrillo González (Fundación para el Desarrollo de la Enfermería, 2011)
The high costs of intensive care and the importance of patient safety and quality of care highlight the need to develop instrument to measure, as precisely as possible, nursing workload and staffing levels in intensive care. To assess the ideal staff number, we need instruments to measure the real nursing workload. The aim of this research is to compare two nursing workload measurement scales in Intensive Care Units, the Nursing Activities Score (NAS) and Nine Equivalents of Nurse Manpower Use Score (NEMS). We also want to assess the staffing needs of our ICU. A descriptive correlational study will be performed in a mixed medical ICU. The sample will be composed of of a minimum of 70 patients. Data regarding individual patients and unit global workload will be recorded, measured both with the NEMS and NAS scales. The required nursing staff will be calculated according to the measured workload. Nursing staffing needs using both scales will be calculated and compared to the actual staff. A descriptive analysis of the variables will be performed, and the existing correlation between both scales will be assessed using the Pearson correlation coefficient. A Student-t test will be performed to determine the differences between the calculated staffing requirements and the actual nursing staff. All data analyses will be done using a statistical software.